The Influence of Strategic Decision-Making Behavior on Internal Negotiation Effectiveness and Organizational Performance in Mining Companies - Gong Zibo; Gallang Perdhana Dalimunthe (Cakrawala Repositori IMWI)
The study was motivated by the complexity and uncertainty of the mining industry, which requires organizations to develop effective decision-making processes and strong internal coordination to achieve sustainable performance. Although strategic decision-making has been widely recognized as an important determinant of organizational success, limited research has examined the mediating role of internal negotiation effectiveness, particularly within the mining sector. This study employed a quantitative approach with a causal-associative research design. Data were collected through a structured questionnaire distributed to 200 employees involved in strategic decision-making and internal coordination processes. Respondents were selected using purposive sampling, and data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the direct and indirect relationships among variables. The results showed that strategic decision-making behavior had a positive and significant effect on organizational performance and internal negotiation effectiveness. Furthermore, internal negotiation effectiveness positively influenced organizational performance and significantly mediated the relationship between strategic decision-making behavior and organizational performance. These findings indicated that effective strategic decisions produced stronger performance outcomes when supported by effective internal communication, collaboration, and negotiation processes. This study contributed to the strategic management literature by highlighting the role of internal negotiation effectiveness as a mechanism that strengthens the relationship between managerial decision-making and organizational performance. Practically, these findings provide valuable insights for mining company managers to improve decision quality and strengthen internal coordination capabilities.